STUDIES ON THE RELATIONSHIP OF ALLOTYPIC SPECIFICITIES TO ANTIBODY SPECIFICITIES IN THE RABBIT - Rieder, Ronald F. (The Rockefeller University Press, 1963)
Purified antibodies against three different antigens and haptens (ovalbumin, dinitrophenol, and Type II pneumococcal polysaccharide) were prepared from specific precipitates from the antisera of several rabbits. The reactions of these preparations with antisera against the allotypic specificities carried by each of the animals forming the antibodies were used to compare the relative concentrations of molecules bearing each specificity in the different solutions of antibodies from each rabbit. These relative concentrations appeared to vary greatly from one preparation to another, although all the allotypic specificities carried by each animal were found in all the preparations of antibodies from that animal. The interpretation of these results is discussed.